2011
DOI: 10.1016/j.catcom.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical instability of Cu3(BTC)2 by reaction with thiols

Abstract: In contrast to Fe(BTC) (BTC: 1,3,5-benzenetricarboxylate), the crystal structure of Cu 3 (BTC) 2 , a commercial metal organic framework widely used as solid catalyst, collapses when contacted with thiols under mild reaction conditions forming copper nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…In another precedent, the crystal structure of Cu 3 (BTC) 2 was collapsed during the aerobic oxidation of thiophenol at 70°C in acetonitrile medium after 10 min due to the strong Cu 2? -thiol bond [13]. We note, however, that in the present case, the experimental conditions are milder, since the reaction is performed at room temperature and the reaction times are comparatively shorter.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In another precedent, the crystal structure of Cu 3 (BTC) 2 was collapsed during the aerobic oxidation of thiophenol at 70°C in acetonitrile medium after 10 min due to the strong Cu 2? -thiol bond [13]. We note, however, that in the present case, the experimental conditions are milder, since the reaction is performed at room temperature and the reaction times are comparatively shorter.…”
Section: Resultsmentioning
confidence: 92%
“…Currently, there is a need to delineate the stability of MOFs compared with zeolites and other related metal oxides with the aim to clarify if MOFs could be used as industrial heterogeneous catalysts. We have already demonstrated that Cu 3 (BTC) 2 undergoes major changes in its crystal structure by forming Cu nanoparticles when reacted with aliphatic/aromatic thiols [13]. Similarly, destruction of Cu 3 (BTC) 2 framework was observed in the oxidation of CO [33].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[17,25] However, there is a paucity of detailed studies on the deactivation of Fe-containing MOFs as catalysts for liquid-phase organic reactions. Recently, we have shown that Cu 3 (BTC) 2 decomposes in the presence of thiophenol, [26] whereas Fe(BTC) is stable under identical experimental conditions effecting the aerobic oxidation of thiophenol to diphenyldisulfide with complete selectivity. [27] Information about deactivation mechanisms and identification of catalytic poisons formed during the course of the catalytic reaction are necessary to assess the stability of the catalyst and the viability of a particular reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Considering that the thermal and chemical stability of MOF is not as high as those of zeolites, the issue of recyclability and catalyst stability is very important in the area of use of MOFs as catalysts and has been specifically addressed in the present review. [37] Considering that the thermal and chemical stability of MOF is not as high as those of zeolites, the issue of recyclability and catalyst stability is very important in the area of use of MOFs as catalysts and has been specifically addressed in the present review.…”
Section: Introductionmentioning
confidence: 99%